2017
DOI: 10.1111/nhs.12354
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of difficult conversations among Australian paramedics

Abstract: Previous studies indicate that healthcare professionals find it challenging to engage in difficult conversations regarding concerning behavior of colleagues. As a result, these conversations are often avoided. The inability to have these difficult conversations is associated with poorer patient outcomes, staff commitment, discretionary effort, and employee satisfaction. This descriptive study used an online questionnaire to examine responses of paramedics employed by Ambulance Victoria (Australia) regarding di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Patient-provider communication training has been extensively studied among physicians, and is effective in improving patient satisfaction and compliance (21,22). Past studies on communication training for EMS, however, have focussed primarily on interprofessional communication (23)(24)(25), rather than general patient-EMS interactions. There is a need for further research to develop and test interventions for increasing sensitive responding by EMS when attending to patients who have fainted.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-provider communication training has been extensively studied among physicians, and is effective in improving patient satisfaction and compliance (21,22). Past studies on communication training for EMS, however, have focussed primarily on interprofessional communication (23)(24)(25), rather than general patient-EMS interactions. There is a need for further research to develop and test interventions for increasing sensitive responding by EMS when attending to patients who have fainted.…”
Section: Discussionmentioning
confidence: 99%
“…The participants in this study reported the risk of being seen as a wimp when trying to discuss person-centred issues, as the AS context was characterised as rather tough and medically orientated. A study indicated that ACs find it difficult to raise the issue of bad behaviour on the part of colleagues [36]. The workplace culture can therefore hinder discussions about behaviours in the encounter between colleagues, as well as concerning patients.…”
Section: Discussionmentioning
confidence: 99%
“…13 In the out of hospital setting, research into medical error has largely focused on medication safety and clinical error. [14][15][16] Beyond this, little has been published on error in paramedicine and its links to patient safety and individual and organisational accountability.…”
Section: Errormentioning
confidence: 99%
“…18 For instance, reporting of errors or near misses may be low due to a perceived lack of psychological safety for the reporters and others involved in the patient safety event. 15 Formal review of errors in healthcare may also, at times, be considered negative or punitive, 19 with participants possibly fearing recrimination for their perceived shortcomings. As has been reported in medication safety incidents, this may in turn lead to under-reporting of error and patient safety events, hindering opportunities for improvement.…”
Section: Errormentioning
confidence: 99%